Análisis de las Particularidades de la Producción y Comercialización del Arroz en Colombia 2010-2018 (2019)
This work seeks to analyse the particularities of rice production and marketing and its impact on the colombian economy between the years 2010 – 2018; for this data consulted in national institutions such as: CIAT (International Tropical Agricultura Center), DANE (National Administrative Department of Statistics. Fedearroz (National Rice federation), ICA (Colombian Agricultural Institute), Induarroz (Rice Industry), MinAgricuktura (Ministry of Agriculture), among other. At the same time, a study of this Research is being carried out to analyse the process of the production chain, this is descriptive, since it makes a precise record of the variables involved in the work.